MRI Predictors of Recurrence and Outcome after Acute Transverse Myelitis of Unidentified Etiology - Bulut, E.; Shoemaker, T.; Karakaya, J.; Ray, D.M.; Mealy, M.A.; Levy, M.; Izbudak, I. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: The early prediction of recurrence after an initial event of transverse myelitis helps to guide preventive treatment and optimize outcomes. Our aim was to identify MR imaging findings predictive of relapse and poor outcome in patients with acute transverse myelitis of unidentified etiology.MATERIALS AND METHODS: Spinal MRIs of 77 patients (mean age, 36.3 ± 20 years) diagnosed with acute transverse myelitis were evaluated retrospectively. Only the patients for whom an underlying cause of myelitis could not be identified within 3 months of symptom onset were included. Initial spinal MR images of patients were examined in terms of lesion extent, location and distribution, brain stem extension, cord expansion, T1 signal, contrast enhancement, and the presence of bright spotty lesions and the owl's eyes sign. The relapse rates and Kurtzke Expanded Disability Status Scale scores at least 1 year (range, 1–14 years) after a myelitis attack were also recorded. Associations of MR imaging findings with clinical variables were studied with univariate associations and binary log-linear regression. Differences were considered significant for P values < .05.RESULTS: Twenty-seven patients (35.1%) eventually developed recurrent disease. Binary logistic regression revealed 3 main significant predictors of recurrence: cord expansion (OR, 5.30; 95% CI, 1.33–21.11), contrast enhancement (OR, 5.05; 95% CI, 1.25–20.34), and bright spotty lesions (OR, 3.63; 95% CI, 1.06–12.43). None of the imaging variables showed significant correlation with the disability scores.CONCLUSIONS: Cord expansion, contrast enhancement, and the presence of bright spotty lesions could be used as early MR imaging predictors of relapse in patients with acute transverse myelitis of unidentified etiology. Collaborative studies with a larger number of patients are required to validate these findings.BSLbright spotty lesionEDSSExpanded Disability Status ScaleLETMlongitudinally extensive transverse myelitisNMOSDneuromyelitis optica spectrum disorder